The Humanities And The University: Craig Calhoun Interviewed. (February 2020) - Vale, Peter
In this interview Craig Calhoun talks about universities, the Humanities and his own research. Universities reinvent themselves in the face of societal and technological change. In the midst of this change, however, universities are charged with maintaining old ideals, with informing the public and creating opportunities for human development. The Humanities often bemoan these changes but they are ideally positioned to contribute to the changing university – especially through teaching – and so protect the traditional place of the university in society. The Humanities must help to defend the canon but, at the same time, be open to new rethinking the canon by embracing alternative epistemologies. One means to do this is to opening knowledge up by embracing languages other than English. Calhoun's own research is focussed on those 'parts of globalisation' that are not commonly investigated: Belonging and Identity, Social Emergencies as an exception; the fragility of Global capitalism.